Seed bio-priming in the management of seed- and soil-borne diseases - PANDEY, R.N. (Indian Phytopathology, 2017)
The use of pesticides in agriculture is restricted due to environmental and health hazards. However, pests need to be managed to harvest healthy crops. Environmental Protection Agency (EPA) in the developed countries encourage the management of the plant diseases and pests throughÂ Â biological control by using the appropriate, efficient and quality bioagents. The bioagents viz. TrichodermaÂ harzianum, T. viride, T. virens, T. atroviride, T. koningii, Paecilomyces lilacinus and Pseudomonas fluorescens, etc have been proved effective for the management of the seed- and soil borne plant pathogens/ diseases. Different workers have worked out the mode of action of the bioagents. Molecular studies have shown that different genes in the bioagents are responsible for their efficiency to manage the pathogens and enhancing the plant growth. The bioagent like T. asperellum has been found to be entophyte in the plant system and perform very well for all these characters. Therefore, a large number of rhizospheric bioagent should be isolated and studies for useful characters of eco-friendly management of biotic and abiotic stresses. The method of use of the bioagents in plant health management should also be studied thoroughly, as seed bio- priming of the bioagents particularly Trichoderma spp. have been found quite effective to manage the plant pathogens and enhancing germination, seedling vigour, plant growth, etc. In the wake of climate change, the bioagents are the hope to overcome the biotic and abiotic stresses and ecofriendly and sustainable management of diseases and plant health. An attempt has been made to summarize the work carried out on seed priming by a different method in general and seed bio-priming in particular and has been presented in this article.